The European Mayor: Political Leaders in the Changing Context of Local Democracy - Bäck, Henry (SpringerLink Bücher, 2006)
With this book we aim at describing and analysing the selection, daily life, networks and values of local top political leaders in seventeen European countries. The empirical nourishment to the investigation into town halls across Europe is a survey conducted in 2003 with mayors and corresponding top local political leaders. The data covering responses from 2700 leaders is a unique and rich material allowing descriptions and analyses pursuing a number of lines of inquiry.